Tripod gait for six-legged robots walking on undulating terrain - Yu SATO; Kenji INOUE (Nihon Kikai Gakkai ronbunshu, 2016)
A method for a six-legged robot of walking on terrain with various undulations by tripod gait is proposed. First the robot detects foot landing using touch sensors, and estimates the inclination angle of the ground from the landing positions; the estimated ground is called “reference ground”. Second the robot measures the inclination angle of its body using acceleration sensor. Then the legs move up and down so that the body may be parallel to and may keep a constant distance from the reference ground. If the robot encounters deep depressions or downward slopes, the robot suspends walking and actively inclines the reference ground. As a result the body inclines, and the swing leg goes further down. When the swing leg reaches the ground, the robot restarts walking. Due to the feedback gain of body orientation control, the robot does not respond to fine change of undulation. Hence the body keeps a constant orientation on short distance undulation or rugged surface, and gradually inclines its body on long distance undulation such as slopes and stairs. The ability of climbing up and down slopes and steps in longitudinal and transverse directions is evaluated by experiments. The maximum angle of climbing up slopes is 30 degree, and that of climbing down slopes is 40 degree. The maximum height of climbing up steps is 150 mm, and that of climbing down steps is 180 mm. The robot can also go through a bump of 125 mm width and 60 mm height.